BENCANA AIR KARENA SALAH URUS - Siti Kusumawati Azhari (Jurnal Sosioteknologi, 2007)
Water is a source of life "“ all creatures rely on it, and any societies deal with it. According to Irrigation Acts, water has fourteen functions including for national security, worships, household, agriculture, animal husbandry, fishery, plantation, forestry, energy, mining, water transportation, and recreation. The pollution of river water, and land water directly affects the health, the declining quality and the quantity of water, and flood. In addition, the indirect effects include stinky water, arid trees, and unidentified diseases. The proprietors of the environment pollution can be charged for criminal, civil, and environmental case. The management of environment should not be conducted partly.